Anti-corruption management in the health care system: the legal aspect - М. А. Anishchenko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2019)
The purpose of the research. To analyze the concept of anti-corruption management and organizational and legal aspects of the implementation of anti-corruption activities in health care institutions, on the basis of the analyzed material, to define the concept of “anti-corruption management in health care institutions”, to determine legal problems in the organization of the indicated activity and to outline ways of their solution.